A Detailed Model of the Irish High Voltage Power Network for Simulating GICs. Issue 11 (9th November 2018) - Blake, Seán P.; Gallagher, Peter T.; Campanyà, Joan; Hogg, Colin; Beggan, Ciarán D.; Thomson, Alan W. P.; Richardson, Gemma S.; Bell, David
Abstract: Constructing a power network model for geomagnetically induced current (GIC) calculations requires information on the DC resistances of elements within a network. This information is often not known, and power network models are simplified as a result, with assumptions used for network element resistances. Ireland's relatively small, isolated network presents an opportunity to model a complete power network in detail, using as much real‐world information as possible. A complete model of the Irish 400, 275, 220, and 110 kV network was made for GIC calculations, with detailed information on the number, type, and DC resistances of transformers. The measured grounding resistances at a number of substations were also included in the model, which represents a considerable improvement on previous models of the Irish power network for GIC calculations. Sensitivity tests were performed to show how calculated GIC amplitudes are affected by different aspects of the model. These tests investigated: (1) How the orientation of a uniform electric field affects GICs. (2) The effect of including/omitting lower voltage elements of the power network. (3) How the substation grounding resistances assumptions affected GIC values. It was found that changing the grounding resistance value had a considerable effect on calculated GICs at some substations and no discernible effect at others. Finally, five recent geomagnetic storm events were simulated in the network. It was found that heavy rainfall prior to the 26–28 August 2015 geomagnetic storm event may have had a measurable impact on measured GIC amplitudes at a 400/220 kV transformer ground. Key Points: A detailed model of the Irish 400, 275, 220, and 110 kV power network was developed for GIC simulations The impact of assumptions used to construct a power network model was evaluated for GIC simulations Heavy rainfall before a 2015 geomagnetic storm may have decreased the grounding resistance at a substation, leading to larger GICs